Preparation and characterization of carbon black nanoparticle-filled electroactive electrospun poly(vinyl alcohol)nanofibers - Surawut chuangchote (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006